SPATIAL DISTRIBUTION OF THE WESTERN JADWAL SOILS PROPERTIES AND SUITABILITY EVALUATION FOR WHEAT CROP CULTIVATION BY GEOMATICS TECHNOLOGY - & et al., Hamad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The study area was chosen in the district of the western Jadwal in Karbala governorate - Iraq, which is located between E44o05'10'' to  E44o13'03'' and  N32o38'30'' to N32o27'40'', as 100 locations were identified for the depth of 0-30 cm by auger hole  sampling method samples were obtained from each site, and kept laboratory measurements. The results of the study showed that the dominant soil texture is medium clay and silt are the predominant separates in the soil. As for the salinity of the soil represented by electrical conductivity, it was low of the dissolution the salts and the land use for cultivation besides the presence of a drainage network a percentage of the organic matter is good. As for assessing the suitability of the land for cultivation, Results showed the use of the standard addition method of land evaluation for the wheat crop by Sys,1993 is better and more accurate than the standard multiplication method for the wheat crop that was also suggested by Sys, 1980, where the very suitable class S1 and the suitable S2 were the predominant cultivars of the addition method, while the non- suitable class N and the least suitable S5 were classes when the methods of multiplication were used.